Student Skills in Utilizing Information Technology in Guidance and Counseling Services as Preparation for the Innovative Technology Consciousness - Ni Made Diah Padmi; Hendry Marthen (Department of Guidance and Counseling, FIP, Undiksha, 2020)
Communication is one of the requirements in the implementation of the Guidance and Counseling service. During the Covid-19 Pandemic, the communication process could only be done through an online, including the Guidance and Counseling service at school. So that the application of Information and Communication Technology in Guidance and Counseling services becomes very important as a means of support in conveying information, namely service materials to support online learning activities. Current technological developments force BK teachers to continuously update their knowledge and skills in utilizing Information and Communication Technology. The purpose of this study is to describe the skills of students in utilizing Information Technology in Guidance and Counseling Services. The research method used is descriptive qualitative to describe the skills of students in utilizing various Information and Communication Technology facilities that can support Guidance and Counseling services in schools. Based on the research carried out, it was obtained an average score of 69 in the high, medium and low categories. Of the 70 students who participated, it showed that 51%, namely 36 students, had a score below the average ≤ 69.